Assessing COVID-19 seroprevalence and vaccine uptake among women of reproductive-age in Zanzibar's archipelago. - Karim Manji; Ame Masemo Ame; Sayan Das; Ali Salim Ali; Navdeep Singh; Fahad Aftab; Arup Dutta; Saikat Deb (PLOS Global Public Health)
Recent events in public health globally have created a need for response by public health researchers in all disciplines to evaluate impact on health, morbidity and mortality of the COVID-19 pandemic that has engulfed the world after 100 years of previous influenza pandemic. Most of the immediate responses, globally; have focused on diagnosis and management of severe cases. However, for evolution of policies dealing with population health in the post COVID-19 era, community-based data for rates of morbidity, risk factors of illness and severity and outcomes of influenza like illness in Maternal, Neonatal and Child Health (MNCH) is needed to inform evidence-based policy. This pilot project aimed to collect preliminary data on seroprevalence from the two island populations of Tanzania. The proposed pilot, cross-sectional, facility-based study obtained a random sample of 1082 women of reproductive age visiting PHCUs from Unguja and Pemba. A total of 25 PHCUs were randomly selected among the 98 PHCUs. Venus blood sample was collected and a information related to recent history of covid-19 symptoms were collected in questionnaire from these women. The blood samples were processed for obtaining serum, which were tested for IgG and IgM antibodies at the PHl-CPHK laboratory in Pemba Island The overall IgG seroprevalence was 90.76% (95% CI: 89.01-92.51); Pemba: 92.91% (95% CI: 90.61-95.22), Unguja: 88.29% (95% CI: 85.38-91.20).There is minor non-significant difference in exposure between Unguja and Pemba in spite of large difference in tourist inflow between the islands. Severity profile and mortality experience is substantially lower in Zanzibar. The prevalence of Vaccination in community is Low and disinformation seems to be the main cause rather than reluctance. There is no significant relation with respect to symptomatology amongst seropositive along with their vaccination status.